Myocardial infarction in patients with HIV infection: incidence, risk factors, pathogenesis, clinical performance and treatment - K. V. Protasov; E. S. Eniseeva; Yu. K. Plotnikova (Российский кардиологический журнал, 2024)
HIV infection increases the risk of premature myocardial infarction (MI) and other atherosclerotic cardiovascular diseases, which are the main noncommunicable cause of death in HIV-infected patients. The review presents the analysis of recent literature on the incidence, prevalence and risk factors of MI in HIV-infected people. It established that MI is associated with the combined effects of traditional cardiovascular risk factors, HIV infection and the cardiometabolic effects of antiretroviral therapy. Pathogenetic features of acute coronary syndrome in HIV infection under conditions of systemic immune-mediated inflammation, hypercoagulation and direct exposure to the virus are highlighted. The clinical features and coronary damage in MI are described. Methods of treating MI are compared. We concluded that the volume and quality of care for patients with HIV and MI is insufficient. From the perspective of possible drug interactions with antiretroviral therapy, effectiveness and safety of methods for secondary prevention of MI was analyzed.